Improving the water productivity of livestock: an opportunity for poverty reduction - Peden, Donald G.; Tadesse, G.; Mammo, M. (International Livestock Research Institute, 2003)
In Ethiopia, intensification of agricultural production is the primary focus of the government’s poverty reduction strategy. Livestock constitute an invaluable resource providing essential goods and services to small-scale poor farmers and their families and communities. Production of high valued livestock products provides a route out of poverty especially where growing urban demand fuels the markets. Water security is a requisite input for livestock production and its resultant contribution to poverty reduction. Typically, one tropical livestock unit (TLU = 250 kg live weight) requires less than 50 litres/day derived from drinking water and moisture in animal feeds. Assuming annual rainfall of 500 to 1000 mm and a stocking rate of one TLU/ha, the drinking water required by livestock is less than 0.2% of the intercepted precipitation. While sufficient high quality water is essential to sustaining livestock production, direct water intake is only of minor significance in terms of livestock water budgets in farming systems and watersheds where the water required for feed production can be up to 5000 litres/TLU per day or 100 times the amount directly consumed.